Treatment of high cervical arteriovenous fistulas in the craniocervical junction region - Su, Han; Yu, Jinlu (Frontiers in Neurology, 2023)
The craniocervical junction (CCJ) is a complex region. Rarely, arteriovenous fistulas (AVFs) can occur in the CCJ region. Currently, it is accepted that CCJ AVFs should only refer to AVFs at the C1-C2 levels. It is reasonable to assume that high cervical CCJ AVFs are being referred to when discussing CCJ AVFs. High cervical CCJ AVFs can be divided into the following four types: dural AVF, radicular AVF, epidural AVF and perimedullary AVF. Until now, it was difficult to understand high cervical CCJ AVFs and provide a proper treatment for them. Therefore, an updated review of high cervical CCJ AVFs is necessary. In this review, the following issues are discussed: the definition of high cervical CCJ AVFs, vessel anatomy of the CCJ region, angioarchitecture of high cervical CCJ AVFs, treatment options, prognoses and complications. Based on the review and our experience, we found that the four types of high cervical CCJ AVFs share similar clinical and imaging characteristics. Patients may present with intracranial hemorrhage or congestive myelopathy. Treatment, including open surgery and endovascular treatment (EVT), can be used for symptomatic AVFs. Most high cervical CCJ AVFs can be effectively treated with open surgery. EVT remains challenging due to a high rate of incomplete obliteration and complications, and it can only be performed in superselective AVFs with simple angioarchitecture. Appropriate treatment can lead to a good prognosis.